Hidratated open cell phenolic foam as a mean to mitigate water stress in Pinus leiophylla seedlings - Palacios-Romero, Abraham; Rodríguez-Laguna, Rodrigo; Razo Zárate, Ramón; Meza-Rangel, Joel; Prieto-García, Francisco; Hernández Flores, María de la Luz (Instituto de Ecología, A.C., 2017)
This study aimed to determine the effect of open cell phenolic foam as a mechanism to mitigate water stress in Pinus leiophylla seedlings under greenhouse conditions. A test procedure was established, in which plants produced with this system were used and four treatments of different phenolic foam volume and a control were applied. Survival, growth in height, diameter and increase in biomass were evaluated weekly. Significant differences were found in survival time between treatments; the time to 50% survival of individuals was increased up to six to seven weeks when phenolic foam hydrated 462 cm3 and 616 cm3 was applied compared with the control. As for growth in height and diameter, the control again had the lowest growth in height and diameter (29.5 cm and 4.1 mm, respectively) compared to other treatments, while plants with foam of 462 cm3 showed the highest growth in height and diameter (33.5 cm y 5.1 mm, respectively). In the case of biomass, plants with 308 cm3 foam showed the lowest value compared with those of foam of 616 cm3 and control. These results suggest that the phenolic foam is effective for mitigating the effects of water stress since seedling survival was increased up to seven weeks and growth in height and diameter was improved when compared with the control.